A cross-sectional study on patient-centered care in a selected hospital in eThekwini district, KwaZulu-Natal, South Africa - Marcel Peruma; Waheedha Emmamally; Mildred Mooi; Uchenna B. Okafor (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Clinical healthcare reform demands high-quality patient care, especially in emergencies. Patient-centred care (PCC) prioritises therapy based on health, characteristics, and needs.